Silver sequestration of halides for the activation of Pd(OAc) 2 catalyzed Mizoroki-Heck reaction of 1,1 and 1,2 - Disubstituted alkenes: Ag Sequestration for Pd catalyzed Heck reaction- disubstituted alkenes - Bangar, Pronnoy G.; Jawalkar, Priyanka R.; Dumbre, Swapnil; Patil, Dharmaraj; Iyer, Suresh (Applied Organometallic Chemistry, 2017)
A ligand free catalytic system consisting of Pd(OAc)2 (cat) and stoichiometric quantities of silver salts, AgOAc or AgBF4, exhibit high efficiency in the Mizoroki-Heck arylation, transforming aryl iodides and 1,1 as well as 1,2 disubstituted alkenes into 1,1,2 – trisubstituted aryl alkenes in excellent yields in very short reaction times.
Keywords: 1; 1-disubstituted alkenes; 2-disubstituted alkenes; AgBF4; AgOAc; Mizoroki-Heck reaction

Mizoroki-Heck reaction of 1,2-disubstituted aryl alkenes: variables of synthesis, solvent and ligand modulation of reactivity - Bangar, Pronnoy G.; Jawalkar, Priyanka R.; Dumbre, Swapnil R.; Raut, Pallavi K.; Patil, Dharmaraj J.; Tv, Neethu; Sudhakaran, Shana; Iyer, Suresh (Synthetic Communications, 2020)
Reaction of aryl iodides with 1,2-disubstituted aryl alkenes in the presence of TBABr/TBACl gave high yields of the Mizoroki-Heck product. Phosphine ligands were used for the modulation of reactivity and stereoselectivity, for the reaction of 4-iodoanisole with cinnamaldehyde. tert-Bu3P.HBF(4)gave the highest E:Z ratio of 1:0.08. The use of PEG-200 and PEG-400 as solvent could activate the reaction of aryl iodides with various 1,2-disubstituetd aryl alkenes.
Keywords: 12-Disubstituted aryl alkenes; 400; ligand effect; Mizoroki-Heck reaction; PEG 200; TBABr

Oxime ligands for Pd catalysis of the mizoroki-heck reaction, suzuki-miyaura coupling & annulation reactions - Bangar, Pronnoy G.; Nahide, Pradip D.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Synthetic Communications, 2021)
Monodentate and bidentate chelating oximes are readily available ligands for the Pd catalysis of the Mizoroki-Heck reaction and the Suzuki coupling. High yields were obtained in the Suzuki coupling in aqueous dioxane with TBABr as additive. The oximes can be easily synthesized from the corresponding ketones or aldehydes and thus provide a very large number of nitrogen-based ligands. They have the advantage of not undergoing oxidative degradation, common for phosphine ligands. Chelating oximes with Pd(OAc)(2), activate aryl iodides to give high yields of the substitution products in the Mizoroki-Heck reactions as well as the Suzuki coupling. Acetophenone oxime ligand with Pd(OAc)(2), catalyzed the reaction of aryl iodides with 1,2-disubstituted alkenes in moderate to high yields. As a test example, the LaRock indole annulation and synthesis of isocoumarin were achieved with acetophenone oxime ligand and Pd(OAc)(2)in high yields.
Keywords: Isocoumarin; LaRock annulation; Mizoroki-Heck reaction; oximes; Suzuki coupling

Oxime ligands for Pd catalysis of the mizoroki–heck reaction, Suzuki–Miyaura coupling & annulation reactions - Bangar, Pronnoy G.; Nahide, Pradip D.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Synthetic Communications, 2021)
AbstractMonodentate and bidentate chelating oximes are readily available ligands for the Pd catalysis of the Mizoroki–Heck reaction and the Suzuki coupling. High yields were obtained in the Suzuki coupling in aqueous dioxane with TBABr as additive. The oximes can be easily synthesized from the corresponding ketones or aldehydes and thus provide a very large number of nitrogen-based ligands. They have the advantage of not undergoing oxidative degradation, common for phosphine ligands. Chelating oximes with Pd(OAc)2, activate aryl iodides to give high yields of the substitution products in the Mizoroki–Heck reactions as well as the Suzuki coupling. Acetophenone oxime ligand with Pd(OAc)2, catalyzed the reaction of aryl iodides with 1,2-disubstituted alkenes in moderate to high yields. As a test example, the LaRock indole annulation and synthesis of isocoumarin were achieved with acetophenone oxime ligand and Pd(OAc)2 in high yields.